Religions as a "Life Fact": Al-Faruqi's impact on the International Islamic University Malaysia - Mohamed Zein, Ibrahim (Association of Muslim Social Scientists, 2011)
This study addresses the teaching of religion at the International Islamic University Malaysia (IIUM). The program was influenced by the thought and curricula developed along Faruqian lines. It is a program that delves into Faruqi's view of meta-religion rooted in an ethical paradigm giving it universal perspective and approach toward the study of IIUM and the religion study curriculum implemeted at IIUM is a development of Faruqi's earlier vision regarding the teaching of Islam as a civilization and worldview, which he had envisioned and hoped to apply to the academic program at the Central Instiute of Islamic Research,Karachi, Pakistan during his professorship there in 1960s, but which was not realized.